Mother to Child Non-Vascularized Fibula Transfer in Congenital Pseudoarthrosis of Tibia - Mohammed Sadiq; Anudeep Manne; Rohith Reddy Kasam; Kothalanka Udaya Kumar; Libin Bernnabas (Journal of Orthopaedic Case Reports)
Introduction: Congenital pseudoarthrosis tibia (CPT) is a relatively rare disease, characterized by anterolateral bowing of the tibia, non-union, and limb length discrepancy. Various surgical treatments have been described in literature for its management with differing favorable outcomes. Case Report: In this report, we present a case of 3-year-old child with CPT of Crawford type IV, with associated fibular dysplasia. Maternal fibula was harvested and used as a bone graft and was stabilized by intra-medullary fixation. Complete union was achieved at 1 year after the primary surgery. No re-fractures were seen in a follow-up period of 2 years. Conclusion: Using maternal fibula as an alternative to use as a bone graft in the management of congenital pseudoarthrosis tibia may prove beneficial. Moreover, it is cheaper and readily available and needs less surgical expertise when compared to its alternatives such as use of bone morphogenetic protein 7, allogenic cadaveric grafting, or use of vascularized fibular graft.